Identification of adenosquamous carcinoma as a rare aggressive HER2-negative subgroup of esophageal/gastroesophageal junction adenocarcinoma - Jin, Zhaohui (Am J Clin Oncol, 2019)
BACKGROUND: Our purpose was to evaluate the prognostic impact of pathologically-confirmed esophageal adenosquamous carcinoma (ASC) and its association with HER2 status and clinicopathologic characteristics. METHODS: Among 796 patients with esophageal or gastroesophageal junction (GEJ) adenocarcinoma who underwent curative resection, surgical pathology reports were reviewed, and suspected ASC was confirmed utilizing p63 and CK5/6 immunostaining. HER2 status was determined using immunohistochemistry and fluorescence in situ hybridization. Cox models were used to assess the impact of ASC on disease-specific survival (DSS) and overall survival (OS). RESULTS: Overall, 2.0% (16/796) of patients had esophageal ASC, mostly demonstrating a close intermingling of squamous and adenocarcinoma cells within the same tumor. The percentage of squamous vs adenocarcinoma cells in the primary was generally recapitulated in nodal metastases, and intrapatient internodal heterogeneity was uncommon. Patients with esophageal ASC were statistically significantly more likely to be female (vs male), have normal (vs excess) body-mass index, and harbor HER2-negative (vs –positive) tumors, as compared to patients with adenocarcinoma-only. No ASC tumor was HER2-positive as compared to 16% of adenocarcinoma-only tumors (P =.018). Compared to patients with adenocarcinoma-only, those with ASC demonstrated profoundly worse DSS (5-year event-free rate: 34% vs 6%; multivariate hazard ratio 2.87 [95% confidence interval 1.59 to 4.76]; P=.0010) and OS (P=.0027) that was independent of known prognostic factors and HER2 status. CONCLUSION: Adenosquamous carcinoma identifies a rare aggressive HER2-negative subgroup of esophageal/GEJ adenocarcinoma.